Anxiety and Depressive Disorders and Quality of Life Assessment of Poles—A Study Covering Two Waves of the COVID-19 Pandemic - Babicki, Mateusz; Bogudzińska, Bogna; Kowalski, Krzysztof; Mastalerz-Migas, Agnieszka (Frontiers in Psychiatry, 2021)
Background: More than a year after the first case of SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2) viral pneumonia, the world is still engulfed by the pandemic, and we know that this condition has an enormous impact not only on individuals but also on the social order in virtually every aspect of daily life, deteriorating our mental health. This study aims to assess the prevalence of depressive and anxiety symptoms and the subjective assessment of the quality of life in the different stages of the COVID-19 (Coronavirus Disease 2019) pandemic based on a nationwide online survey. Materials and Methods: The study was conducted using an original questionnaire assessing the sociodemographic status and standardised psychometric tools: Beck Depression Inventory (BDI), Generalised Anxiety Disorder (GAD-7) and Manchester Short Assessment of Quality of Life (MANSA). The study was conducted in two stages corresponding to the first and second wave of the COVID-19 pandemic. Results: In total, 4083 respondents participated in the survey. The first observation stage took place between 17 and 26 April 2020 and comprised 2457 respondents; the repeated survey that took place between 1 and 30 December 2020 comprised 1626 respondents. In both cases, women constituted the majority of respondents (82.5% in the first stage and 79.6% in the second stage). Statistically significantly higher levels of depression and anxiety were found in second stage, with mean scores of BDI and GAD-7. In the case of MANSA, participants in the different stages of the pandemic showed no significant differences in terms of mean scores. However, women were more susceptible to developing the depression and anxiety symptoms and it was obtained in both waves of the pandemic Conclusions: As the Covid-19 pandemic progressed, there was higher level of depressive and anxiety symptoms among Poles.